職前英語教師透過英語補救教學的教案設計和教學實踐建構專業認同 Pre-Service English Teachers' Professional Identity Construction through Lesson Design and Delivery of English Remedial Education - 簡靜雯 Chin-Wen Chien (National Changhua University of Education, 2016)
教師認同影響語言教學，教師的認同影響他們如何看待他們自己在專業工作和職場生活中。本文探討在臺灣北部語言師資培育課程中的32 位職前英語教師，透過英語補救教學的教案設計和教學實踐實施於六位國小六年級學生之建構專業認同。透過分析撰寫的隱喻、職前英語教師的期末報告和訪談，本研究有下列結論：第一、職前英語教師的認同從原本的英語老師、大姐姐或大哥哥，到最後是英文老師。這樣的認同建構與某些要素相關[ 符合六年級學生需求和幫助他們喜歡學英文]、權威來源[ 大學課程、大學教授、小學 輔導老師、小組成員、教室觀察] 以及自我練習[ 教學練習、教案和教具製作]。為了幫自我助英文老師在多變和社會情境下建構認同，本研究提出兩點建議。 Teacher identity affects how language teaching is played out. Teachers' identity influences how they view themselves in terms of their professional work and lives. This study explored 32 pre-service English teachers' professional identity construction through lesson design and the delivery of remedial education to six elementary school sixth-graders in a language teacher education program in a northern city in Taiwan. On the basis of analysis of the written metaphors, pre-service teachers' final projects, and interviews, this study offers the following major findings. First, these preservice English teachers' identity was constructed by changing from being an English teacher and a big brother or sister to simply being an English teacher. Such identity construction was closely interrelated with their substance (meeting sixth graders' needs and helping them enjoy learning English), their authority source (university course, university instructor, cooperative teacher, team members, classroom observation), and self-practice (teaching practice, lesson plan, and teaching aid designs). In order to make English teachers' identity constructed in dynamic and social context, two suggestions are made.